Common injuries and ailments of the female athlete; pathophysiology, treatment and prevention - Hilibrand, M. J.; Hammoud, S.; Bishop, M.; Woods, D.; Fredrick, R. W.; Dodson, C. C. (The Physician and Sportsmedicine, 2015)
With increasing numbers of women competing in high school and collegiate athletics, it is important that physicians become familiar with injury patterns and medical conditions unique to the female athlete. Observations and clinical data have elucidated unique biomechanical, anatomic and hormonal factors that predispose skeletally mature female athletes to anterior cruciate ligament (ACL) injuries, patellofemoral disorders and lower extremity stress fractures. Additionally, younger female athletes are particularly at risk of developing components of the "Female Athlete Triad" (more recently included under the syndrome of "Relative Energy Deficiency in Sport" [RED-S]): disordered eating, amenorrhea and osteoporosis. An understanding of the pathophysiology of these conditions has led to the development of programs that can treat their underlying causes, decrease susceptibility to injury, and improve the long-term health of the female athlete. This paper is intended to provide physicians with a review of the sex-specific etiology, prevention and treatment of injuries common to the female athlete.